Minangkabau Women Characters In the Novel Sitti Nurbaya (Love Isn't Up To) Rusli's Angry Works - ., Aimifrina; Bandung, AB.Takko; Maknun, Tadjuddin; Badaruddin, Muhammad Syafri (International Journal of Membrane Science and Technology, 2023)
The goal of this study is to describe the Minangkabau ladies in Marah Rusli's novel Sitti Nurbaya (Unacceptable Love) as they are represented by the various Minangkabau culture members. One of the tribes in Indonesia that has a matrilineal kinship structure is the Minangkabau. Variety of persons is a subjective human evaluation that deviates from the Minangkabau philosophy's principles. There are four different kinds of people: humble, haughty, haughty, and people. Bundo kanduang refers to Minangkabau women as viewed via the matrilineal kinship structure. Bundo Kanduang possesses the virtues of patience, wisdom, caution, and compassion. This study uses a qualitative descriptive research design, a descriptive-analytical approach, and data-gathering strategies including taking notes in the library. The study makes use of ethnographic research Thus, the data analysis technique is to determine literary works that display many ethnographic aspects that reflect traditional life that has taken root in the hearts of its owners; examined the issues of thought, ideas, philosophy, and the premises of society which are reflected in literary works; paying attention to story structure; analysis of the variety of people and traditions that characterize society; an analysis of a woman called bundo kanduang to find out the four characteristics of her bundo kanduang; description of the results of the study and concluding the results of the research. The results of the study concluded that five out of the six Minangkabau women in the novel Sitti Nurbaya (Unacceptable Love), namely Sitti Nurbaya, Putri Rukiah, Sitti Maryam, Sitti Alimah, and Fatimah belong to the category of people, while Putri Rubiah is included in the category of people. Furthermore, of the six women who are called bundo kanduang are Putri Rukiah, Sitti Maryam, and Fatimah who has the characteristics of bundo kanduang are Sitti Maryam (wise, wise and patient) and Fatimah (wise and patient).